Worker injuries involving the interaction of cattle, cattle handlers, and farm structures or equipment - Fox, Shannon L.; Ricketts, Mitchell S.; Minton, J. Ernest (My University, 2015)
Cattle have been identified as leading sources of injuries to agricultural workers. The present study focused on worker injuries that involved the interaction of cattle, cattle handlers, and farm structures or equipment. The goal of the study was to identify opportunities for injury prevention. We examined 221 reports of injury to cattle handlers from the Consumer Product Safety Commission’s National Electronic Injury Surveillance System (NEISS). Expected interactions led to many of the cattle-handling injuries reported in the NEISS database. In almost 30% of cases, cattle pushed workers into structures such as fences, gates, posts, and walls. In another 16% to 19% of injuries, cattle struck gates and other objects, propelling them at the victims. The present research makes several important contributions to the study of cattle-handling injuries. First, the research supports an increased emphasis on the development of safer gate designs (e.g., gates that are remotely operated or that absorb energy to limit the speed at which they may be propelled by animals). Second, the research suggests a need for additional study of energy-absorbing fence and wall structures. We view these two points to be of significance because gates and associated structures (e.g., posts, fences, and walls) accounted for 45% of the injuries in the dataset, based on the associated injury narrative. Finally, the research identifies a previously unexplored source of agricultural injury data, namely the NEISS database.
Keywords: Agricultural accidents; Agricultural injuries; Cattle; Cattle handling; Farm accidents; Farm injuries; Safety